Noncash Income, Living Standards, and Inequality: Evidence from the Luxembourg Income Study - Michael Wolfson; Peter Saunders; Stephen Jenkins; Aldi Hagenaars; Richard Hauser; John Coder; Johan Fritzell; Timothy Smeeding (Luxembourg Income Study (LIS), 1992)
A cooperative comprehensive study by a group of researchers under the Luxembourg Income Study, aimed at summarizing the impact of noncash income on living standards and poverty in seven western nations. Emphasis in data analysis is placed on the life cycle perspective. The study also focuses on comparison of the distribution of noncash income across countries.
Keywords: 330